Education, skills and labour market outcome in Indonesia: An instrumental variable approach - Tri Mulyaningsih; Dhian Adhitya; Amelia Choya Tia Rosalia (Universitas Islam Indonesia, 2021)
Purpose - This study examines the contribution of schooling and skills to earnings. Importantly, this study captures the importance of observing cognitive skills and non-cognitive skills associated with personality traits in determining earnings.Methods - A revised Mincer Model serves as a theoretical framework to explain the contribution of schooling and skills to earnings. Using the Indonesian labour data from the 5th wave of Indonesian Family Life Survey (IFLS), the 2-Stage Least Squares is employed to measure the effects of schooling, cognitive and non-cognitive skills on earnings.Findings - The results show that schooling and skills, both cognitive and personality traits determine the labour market outcomes. In addition, the relationship between education and earning is nonlinear, suggesting that the returns on education varied across education levels.Implication - The policy should aim to enhance human capital by improving knowledge, cognitive and non-cognitive capacities to assist students in achieving their full potentials.Originality - This study contributes to the literature by measuring the effects of unobservable cognitive skills and non-cognitive skills on earnings in developing countries absent in the previous studies. This study also utilizes the instrumental variable approach of 2-Stage Least Squares to deal with omitted variable bias and the endogeneity problem in the basic Mincer model.